An introduction to Theory and Application of Quantum Mechanics - Yariv, Amnon (Dover Publications, 2013)
Based on a California Institute of Technology course, this outstanding introduction to formal quantum mechanics is geared toward advanced undergraduates in applied physics. The text addresses not only the basic formalism and related phenomena but also takes students a step further to a consideration of generic and important applications. The treatment's exploration of a wide range of topics culminates in two eminently practical subjects, the semiconductor transistor and the laser. Subjects include operators, Eigenvalue problems, the harmonic oscillator, angular momentum, matrix formulation of quantum mechanics, perturbation theory, the interaction of electromagnetic radiation with atomic systems, and absorption and dispersion of radiation in atomic media. Additional topics include laser oscillation, quantum statistics, applications of the statistical distribution laws, the interaction of electrons and nuclei with magnetic fields, and charge transport in semiconductors. Each chapter concludes with a set of problems.